Analisis Faktor-Faktor yang Memengaruhi Pergeseran Nilai Moral Remaja di Era Digital - Rusdiana Rusdiana; Zainul Akhyar (Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the factors influencing the shift in adolescents' moral values in the digital era. A qualitative approach with a descriptive method was employed. The study involved 13 informants, including the village head, neighborhood association (RT) leaders, parents, and adolescents, who were selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that the shift in adolescents' moral values is reflected in declining politeness, weakened sense of responsibility, reduced adherence to social norms, and decreased participation in religious and social activities. The factors contributing to this phenomenon include the high intensity of digital media use, peer influence, weak social control, and inadequate parental supervision. Therefore, collaborative efforts among families, schools, communities, and other stakeholders are essential to strengthen character education and promote digital literacy among adolescents.